Molecular Cloning and Expression Analysis of Ethylene-Insensitive3-Like 1 (ScEIL1) Gene in Sugarcane - Fan-Wei Wang; Jian-Bin Yu; Dong Xiao; Yang-Rui Li; Long-Fei He; Ai-Qin Wang (Sugar Tech, 2019)

The T cell activating properties and antitumour activity of Staphylococcal Enterotoxin-like Q - Yanan He; Yuliang Sun; Yakun Ren; Liang Qiao; Rui Guo; Jiang Du; Xinxing Zhu; Yanli Liu; Juntang Lin (Medical Microbiology and Immunology, 2019)

Comparative Transcriptome Analysis of Tree Peony Petals on Two Different Rootstocks - Yan Li; Yihong Chang; Jiuxing Lu; Rui Wang; Dan He; Qiusheng Yang; Yonghua Li (Journal of Plant Growth Regulation, 2019)

Pedobacter changchengzhani sp. nov., isolated from soil of Antarctica - Rui-Han He; Zhen-Wei Liu; Yong Yu; Hui-Rong Li; Zong-Jun Du (Antonie van Leeuwenhoek, 2019)

Model Tests on the Frequency Responses of Offshore Monopiles - Rui He; Tao Zhu (Journal of Marine Science and Engineering, 2019)
Monopiles are widely used to support offshore wind turbines as a result of the extensive development of offshore wind energy in coastal areas of China. An offshore wind turbine is a typical high-rise structure sensitive to dynamic loads in ocean environment such as winds, water waves, currents and seismic waves. Most of the existing researches focus on elastic vibration analysis, bearing capacity or cyclic degradation problems. There’re very few studies on vibration of monopiles, especially considering the influence of static loads with different amplitudes, directions, and loading-unloading-reloading processes. In this paper, laboratory-scale 1 g model tests for a monopile in dry sands were carried out to investigate the frequency responses of the monopile under different loading conditions. The bearing capacities of the model monopile were obtained as references, and dynamic loads and static loads with different amplitudes were then applied to the monopile. It was found that (1) the first resonant frequency of the monopile decreases with the increase of dynamic load amplitudes; (2) the first resonant frequency of the monopile steadily increases under the lateral static load and loading-unloading-reloading processes; (3) the frequency responses of the monopile with static loads in different directions are also quite different; (4) damping of the monopile is influenced by the load amplitudes, load frequencies, load directions and soil conditions. Besides, all the tests were conducted in both loose sand and dense sand, and the results are almost consistent in general but more obvious in the dense sand case.

ATP induces caspase-3/gasdermin E-mediated pyroptosis in NLRP3 pathway-blocked murine macrophages - Chen-Ying Zeng; Chen-Guang Li; Jun-Xiang Shu; Li-Hui Xu; Dong-Yun Ouyang; Feng-Yi Mai; Qiong-Zhen Zeng; Cheng-Cheng Zhang; Rui-Man Li; Xian-Hui He (Apoptosis, 2019)

Nitrogen use-inefficient oilseed rape genotypes exhibit stronger growth potency during the vegetative growth stage - Xiao Guo; Huiying He; Rong An; Yuying Zhang; Rui Yang; Lanqin Cao; Xiaoming Wu; Biyun Chen; Hui Tian; Yajun Gao (Acta Physiologiae Plantarum, 2019)

Crystal structure of norsethite-type BaMn(CO3)2 and its pressure-induced transition investigated by Raman spectroscopy - Wen Liang; Lin Li; Yuan Yin; Rui Li; Zeming Li; Xiqiang Liu; Chaoshuai Zhao; Shuguang Yang; Yong Meng; Zengsheng Li; Yu He; Heping Li (Physics and Chemistry of Minerals, 2019)

Material Flow and Spatial Data Analysis of the Petroleum Use to Carbon Dioxide (CO 2 ) Emissions in Northeast China - Guang‐xin Liu; Ming Wu; Feng‐rui Jia; Qiang Yue; He‐ming Wang (Journal of Industrial Ecology, 2019)
Summary This study investigated the petroleum consumption and petroleum‐related CO 2 emissions (PCOEs) in Northeast China at city level using material flow analysis (MFA) and spatial data analysis (SDA). The petroleum flows for the year 2014 were plotted, and then the spatial patterns, weighted mean centers (WMCs), and spatial autocorrelations of petroleum consumption and PCOEs were calculated, respectively. It was found that Northeast China is a petroleum exploitation‐processing‐export region in China; the total input of petroleum flows comprised two parts—exploitation (about 60%) and import (about 40%). About one third of the total product oil supply flowed into other provinces. In the consumption process, the product oil was dominated by two sectors: the industry sector (45.5%) and the transportation sector (31%). The rate of PCOEs was 36.69 million tonnes in the waste discharge process. Meanwhile, the WMCs of the petroleum consumption and the PCOEs were located in the south of Northeast China. The location of the petroleum pipelines was the factor shown to determine the spatial patterns of petroleum consumption and PCOEs and the hotspots were distributed along the petroleum pipeline, especially in the Circum‐Bohai Sea regions. Economic development in these regions shows a positive dependence on petroleum consumption and generates larger PCOEs. The findings obtained in this study could provide important decision‐making support to low‐carbon development in Northeast China.

Optimizing cold storage of the ectoparasitic mite Pyemotes zhonghuajia (Acari: Pyemotidae), an efficient biological control agent of stem borers - Limin He; Litao Li; Lichen Yu; Xiong Z. He; Rui Jiao; Changxin Xu; Linlin Zhang; Jinli Liu (Experimental and Applied Acarology, 2019)

Different sources of rural household energy consumption and influencing factors in Dazu, China - Jianjun Jin; Rui He; Foyuan Kuang; Xinyu Wan; Jing Ning (Environmental Science and Pollution Research, 2019)

Mechanical Effect Analysis and Comparative Site Tests on Surrounding Rock with Different Bolt Anchoring Lengths and Pre-tightening Forces - Qi Wang; Hongtao Wang; Rui Pan; Shucai Li; Manchao He; Bei Jiang; Qian Qin; Chong Zhang; Yingdong Xu (Geotechnical and Geological Engineering, 2019)

Dynamic Impedances of Offshore Rock-Socketed Monopiles - Rui He; Ji Ji; Jisheng Zhang; Wei Peng; Zufeng Sun; Zhen Guo (Journal of Marine Science and Engineering, 2019)
With the development of offshore wind energy in China, more and more offshore wind turbines are being constructed in rock-based sea areas. However, the large diameter and thin-walled steel rock-socketed monopiles are very scarce at present, and both the construction and design are very difficult. For the design, the dynamic safety during the whole lifetime of the wind turbine is difficult to guarantee. Dynamic safety of a turbine is mostly controlled by the dynamic impedances of the rock-socketed monopile, which are still not well understood. How to choose the appropriate impedances of the socketed monopiles so that the wind turbines will neither resonant nor be too conservative is the main problem. Based on a numerical model in this study, the accurate impedances are obtained for different frequencies of excitation, different soil and rock parameters, and different rock-socketed lengths. The dynamic stiffness of monopile increases, while the radiative damping decreases as rock-socketed depth increases. When the weathering degree of rock increases, the dynamic stiffness of the monopile decreases, while the radiative damping increases.

Overexpression of BcbZIP134 negatively regulates the biosynthesis of saikosaponins - Jiao Xu; Su-Rui Wu; Yan-Hong Xu; Zhan-Yu Ge; Chun Sui; Jian-He Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Temperature-control-induced masculinization in tiger puffer Takifugu rubripes - He Zhou; Zixin Zhuang; Rui Zhang; Qizheng Xu; Yuting Liang; Zhiqiang Jiang; Xia Li; Tianyu Ma; Yajuan Li (Journal of Oceanology and Limnology, 2019)

Winter chemical partitioning of metals bound to atmospheric fine particles in Dongguan, China, and its health risk assessment - Lin Huang; Yun-He Bai; Rui-Yue Ma; Ze-Ming Zhuo; Ling Chen (Environmental Science and Pollution Research, 2019)

Artemisinin and its derivatives: a potential therapeutic approach for oral lichen planus - Rui-Jie Ma; Ming-Jing He; Ya-Qin Tan; Gang Zhou (Inflammation Research, 2019)

RNA-Sequencing Analysis Reveals Critical Roles of Hormone Metabolism and Signaling Transduction in Seed Germination of Andrographis paniculata - Jiayun Tong; Rui He; Xiaoting Tang; Mingzhi Li; Tao Yi (Journal of Plant Growth Regulation, 2019)

Paleogene sedimentation changes in Lenghu Area, Qaidam Basin in response to the India–Eurasia collision - Rui Zhao; Si Chen; Hua Wang; Detian Yan; Haiyang Cao; Yin Gong; Jie He; Zhixiong Wu (International Journal of Earth Sciences, 2019)

Genomic characterization and pathogenicity of porcine deltacoronavirus strain CHN-HG-2017 from China - Meng-Jia Zhang; De-Jian Liu; Xiao-Li Liu; Xing-Yi Ge; Anan Jongkaewwattana; Qi-Gai He; Rui Luo (Archives of Virology, 2019)

Isolation and characterization of mineral-dissolving bacteria from different levels of altered mica schist surfaces and the adjacent soil - Yuan Li Wang; Qi Wang; Rui Yuan; Xia Fang Sheng; Lin Yan He (World Journal of Microbiology and Biotechnology, 2019)

Whole body vibration with rest days could improve bone quality of distal femoral metaphysis by regulating trabecular arrangement - He Gong; Rui Zhang; Jiazi Gao; Meng Zhang; Bei Liu; Min Zhang; Dong Zhu (Science China Life Sciences, 2019)